Pengaruh Corporate Governance, Financial Flexibility terhadap Earnings Quality Perusahaan Sektor Bank Indonesia - Rahmalita, Nurul Aisyah; Saiful, Saiful (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the effect of three characteristics of the audit committee, which are audit committee independence, audit committee size, and number of audit committee meetings, which are the implementation of corporate governance and financial flexibility, as independent variables, on earnings quality as the dependent variable. The population in this study are financial companies in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2018–2022. This study uses a purposive sampling method, and the type of data collected in this study is a type of secondary data with the method of collecting documentation studies and literature studies. The data analysis method used in this study is multiple linear regression analysis, which has qualified classical assumption testing. The results of this study indicate that there is no significant impact of the variables of financial flexibility, audit committee independence, and size on earnings quality. Meanwhile, the variable number of audit committee meetings has a positive and significant impact on earnings quality, which, if implemented consistently, will increase earnings quality and reduce attempts to manipulate earnings by company management.